1996
DOI: 10.1159/000121109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Acute Subdural Hematoma in Infant Piglets

Abstract: Traumatic acute subdural hematoma is associated with high mortality in the pediatric population, yet the pathophysiology remains poorly understood. The objective of this study was to develop a pediatric model of acute subdural hematoma, and to evaluate the resultant histopathological changes in the brain. Ten 3-week-old piglets were studied. A 5-mm craniotomy was made in the right frontal skull. A small silastic tube was inserted through the underlying intact dura into the subdural space. A craniotomy was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…26,37,46 Contusion injury, diffuse axonal injury, acute subdural hematoma, and epidural hematoma have been characterized in pigs or piglets. 7,32,33,44,46 The piglet ages selected for this study were based on parallels between pig and human development. These three time points were chosen to help answer the question of when maturational differences occur that might be relevant to injury response; it is not clear from clinical experience whether only infants show different injury patterns or whether vulnerability changes in a continuum or in a step-wise manner.…”
Section: Discussionmentioning
confidence: 99%
“…26,37,46 Contusion injury, diffuse axonal injury, acute subdural hematoma, and epidural hematoma have been characterized in pigs or piglets. 7,32,33,44,46 The piglet ages selected for this study were based on parallels between pig and human development. These three time points were chosen to help answer the question of when maturational differences occur that might be relevant to injury response; it is not clear from clinical experience whether only infants show different injury patterns or whether vulnerability changes in a continuum or in a step-wise manner.…”
Section: Discussionmentioning
confidence: 99%
“…In our large-animal models of TBI, we have demonstrated that cortical impact alone 22,23 or SDH alone causes focal damage, 15 but not the extensive widespread acute hypoxic-ischemic type damage observed in HH. In immature rodents prior to 18 days of age, parental kainic acid (1-6 mg/kg) induced severe, generalized tonic-clonic seizures without any histopathological damage, and limbic seizures and ''red neurons,'' neuronal dropout, and a gliotic reaction and scarring at 18 days of age and thereafter.…”
Section: Discussionmentioning
confidence: 79%
“…In previous models of pediatric brain injury, we demonstrated that neither cortical impact 22,23 nor SDH 48 cause HH, but we have not yet tested the theory that HH could be due to seizures alone.…”
Section: Discussionmentioning
confidence: 84%
“…9,10,30 To date, experimental models and clinical evidence have failed to fully explain the development of HH in association with subdural blood. Animal studies designed to mimic SDH in the immature brain, such as the subdural murine model, in which blood is injected over the cerebral convexity through a burr hole 31 or the cranial window infant piglet model, 32 have failed to lead to HH. Moreover, studies to recapitulate the possible mechanisms of AHT using rat 33 and piglet 34 shaking models have not shown HH.…”
Section: Discussionmentioning
confidence: 99%